ASC annual report 2009/2010 (Annual report Australian Sports Commission, 2010)
The 2009-10 year was again a successful one for both the Australian Sports Commission (ASC) and Australian sport. It was also a pivotal year in terms of setting the direction for the future of Australian sport with the announcement in May 2010 of the government`s new strategy, Australian Sport: The Pathway to Success. This strategy built on the recommendations from the Independent Sport Panel Report released in November 2009 and included the single largest funding increase for Australian sport, committing $325 million over the next four years. The new strategy and associated funding have set the platform for implementation of vital reforms which will take Australian sport forward to new highs in performance and contribution to broader government objectives. The ASC took the opportunity afforded by the Independent Panel`s review and its own previous work on strategic re-positioning to further develop its thinking on system leadership and how to give effect to the panel`s recommendations. The organisation also continued with work to improve its capability to deliver the reforms in conjunction with its system partners. In May 2010, the AIS hosted a high performance sports research workshop involving more than 120 participants from NSOs, state and territory institutes and academies of sport, universities,and Australian sports technology research companies. This workshop set the platform for improved national coordination of high performance research and a focus for the lead-up to future Olympic and Paralympic Games. During the year, the ASC again worked closely with sports to support them in more effective planning and delivery of their high performance programs. Through the Pathways to Podium program strategic review initiative, 18 targeted sports were afforded support and advice to enable them to more effectively lead their high performance programs. The ASC also allocated fi nancial support totalling $4.5 million to more than 500 elite athletes through the Australian Government Sport Training Grant Scheme.